An Analysis of Jasser Auda’s Thought on Maqashid Sharia and Its Implications for Sharia Economic Law - Anas Asy’ari Nashuha; Muthoifin; Mariam Elbanna (Walidem Institute and Publishing, 2025)
Objective: This study aims to analyze the thoughts of Jasser Auda regarding Maqashid Sharia (the objectives of Islamic law) and their implications for the development of Sharia Economic Law in Indonesia. Theoretical framework: As the discourse of Ushul al-Fiqh (Islamic legal theory) continues to undergo contextual reform, the relevance of Maqashid Sharia as a fundamental framework for implementing Islamic law becomes increasingly significant. Jasser Auda offers a paradigm shift by introducing a systems-based approach that reconceptualizes the five classical dimensions of Maqashid into a dynamic and holistic framework. His approach moves away from rigid textualism and towards the realization of values and outcomes that reflect the spirit of Sharia in contemporary contexts. Literature review: The literature review highlights how Auda's model diverges from classical methodologies by focusing on interconnectedness, purposefulness, and context sensitivity. Methods: The research is grounded in a qualitative descriptive methodology. Data were collected from relevant literature, policy documents, and scholarly interpretations of Auda's work. The theoretical framework centers on systems theory, epistemological transformation, and the functional role of Maqashid in legal reform. Results: The findings demonstrate that Jasser Auda’s theory of Maqashid Sharia is highly applicable in revitalizing the role of Islamic law in the contemporary economic domain. In the case of Indonesia, where Sharia economic law is rapidly evolving, Auda’s framework provides an adaptive and value-driven model that supports legal dynamism without compromising foundational principles. Implications: His model also offers practical implications for policy-making, Islamic finance regulation, and economic justice. Novelty: The study contributes novelty by bridging classical Islamic legal philosophy with contemporary legal needs through the lens of systems thinking. This synthesis enhances the responsiveness of Sharia Economic Law to modern challenges and aligns legal goals with the ethical aspirations of Islam.